Baitul Maal Wat Tamwil Sebagai Microfinance Alternative Ummat - latifah, Eny (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2018)
The purpose of this research is to know how far the role and effort of KSPPS BMT BINA UMMAT SEJAHTERA run the vision and mission. To know the role of BMT microfinance in accompanying the entrepreneurial operations. This reseach method using qualitative approach that is descriptive. Where the company date are analyzed and then compared with the theory to produce good sytems and methods in decision making. Method of date validity using triangulation technique. The result of this research is KSPPS BMT BINA UMMAT SEJAHTERA has run its vision and mission. By conducting various activies based on sharia principle, with a system of sale and purchase and profit sharing. Oriented to religious social activities so that KSPPS BMT BINA UMMAT SEJAHTERA has. An important role as a companion in the development at entrepreneurial operations, especially around Paciran Lamongan